Pengembangan Media Ajar Berbasis Budaya Jawa Menggunakan Model Pembelajaran RME untuk Meningkatkan Minat Belajar Siswa Sdn 101956 Sukaramai: Penelitian - Landong, Ahmad; Anggreni, Dewi Rezeki; Astria, Niken Dea; Tazmi , Ayustia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to develop Javanese culture-based teaching media using the Realistic Mathematics Education (RME) learning model to improve students' interest and understanding of flat geometry material in grade V of SDN 101956 Sukaramai. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The developed teaching media was validated by material experts, media experts, and teachers, and was declared very feasible with an average validation score above 4.5. The responses of teachers and students were also very positive, with the majority of students stating that the media was easy to use and interesting. The results of the effectiveness test showed an increase in the average student score from 58.3 (pretest) to 83.7 (posttest), with an N-Gain value of 0.61. These findings indicate that local culture-based teaching media is effective in improving students' interest and learning outcomes in mathematics. This media is also considered contextual, meaningful, and in accordance with the characteristics of elementary school students.